Floral Induction of Mango 'Tommy Atkins' at Submedio Sao Francisco Region, Brazil - Silva, G. J. N.; Souza, E. M.; Rodrigues, J. D. [UNESP]; Ono, E. O. [UNESP]; Mouco, M. A. C.; Lu, P. (Int Soc Horticultural Science, 2013)
Irregular production is a major problem in mango. In an attempt to overcome irregular bearing, effects of two antigibberellins on flowering were evaluated, uniconazole (0.25 g of active ingredient per meter of canopy tree diameter) and paclobutrazol (1.0 g of active ingredient per meter of canopy tree diameter). Treatments were applied as a soil drench using 2 L of solution per tree, in a commercial orchard of 'Tommy Atkins' mango. Treatments were applied after the second vegetative flush commenced, subsequent to pruning. Branch growth was evaluated every 30 days after treatment application up to a maximum period of 90 days. The flowering percentage was recorded at 130 days. Ammonium nitrate (NH4NO3) as a foliar spray (concentration of 0.75%) was applied five times at seven day intervals from 95 to 100 days after treatment application as a dormancy breaking treatment. It was found that both paclobutrazol (PBZ) and uniconazole (UCZ) significantly inhibited the development of vegetative growth compared to the control. Both treatments resulted in identical rates of flowering shoots, 87%; based on results, it can be concluded that the application of antigibberellins (PBZ and UCZ) inhibit vegetative development in mango 'Tommy Atkins', and promote high levels of flowering. Additional tests are being carried out in other farms to confirm these findings, for different cultivars and seasons.
Keywords: plant growth retardants; soil applied; triazole